The epistemic harms of empathy in phenomenological psychopathology - Spencer, L; Broome, M (Springer, 2023)
Jaspers identifies empathic understanding as an essential tool for grasping not the mere psychic content of the condition at hand, but the lived experience of the patient. This method then serves as the basis for the phenomenological investigation into the psychiatric condition known as ‘Phenomenological Psychopathology’. In recent years, scholars in the field of phenomenological psychopathology have attempted to refine the concept of empathic understanding for its use in contemporary clinical encounters. Most notably, we have Stanghellini’s contribution of ‘second-order’ empathy and Ratcliffe’s ‘radical empathy’. Through this paper, we reject the pursuit of a renewed version of ‘empathic understanding’, on the grounds that the concept is fundamentally epistemically flawed. We argue that ‘empathic understanding’ risks (1) error, leading to misdiagnosis, mistreatment and an overall misunderstanding of the experience at hand, (2) a unique form of epistemic harm that we call ‘epistemic co-opting’ and (3) epistemic objectification. To conclude, we propose that empathic understanding ought to be replaced with a phenomenological account of Fricker’s virtuous listening.